Tunable three-dimensional engineered prostate cancer tissues for in vitro recapitulation of heterogeneous in vivo prostate tumor stiffness. (15th July 2022) - Habbit, Nicole L.; Anbiah, Benjamin; Anderson, Luke; Suresh, Joshita; Hassani, Iman; Eggert, Matthew; Brannen, Andrew; Davis, Joshua; Tian, Yuan; Prabhakarpandian, Balabhaskar; Panizzi, Peter; Arnold, Robert D.; et al.
Abstract: In this manuscript we report the establishment and characterization of a three-dimensional in vitro, coculture engineered prostate cancer tissue (EPCaT) disease model based upon and informed by our characterization of in vivo prostate cancer (PCa) xenograft tumor stiffness. In prostate cancer, tissue stiffness is known to impact changes in gene and protein expression, alter therapeutic response, and be positively correlated with an aggressive clinical presentation. To inform an appropriate stiffness range for our in vitro model, PC-3 prostate tumor xenografts were established. Tissue stiffness ranged from 95 to 6, 750 Pa. Notably, xenograft cell seeding density significantly impacted tumor stiffness; a two-fold increase in the number of seeded cells not only widened the tissue stiffness range throughout the tumor but also resulted in significant spatial heterogeneity. To fabricate our in vitro EPCaT model, PC-3 castration-resistant prostate cancer cells were co-encapsulated with BJ-5ta fibroblasts within a poly(ethylene glycol)-fibrinogen matrix augmented with excess poly(ethylene glycol)-diacrylate to modulate the matrix mechanical properties. Encapsulated cells temporally remodeled their in vitro microenvironment and enrichment of gene sets associated with tumorigenic progression was observed in response to increased matrix stiffness. Through variation of matrix composition and culture duration, EPCaTs were tuned to mimic the wide range of biomechanical cues provided to PCa cells in vivo ; collectively, a range of 50 to 10, 000 Pa was achievable. Markedly, this also encompasses published clinical PCa stiffness data. Overall, this study serves to introduce our bioinspired, tunable EPCaT model and provide the foundation for future PCa progression and drug development studies. Statement of significance: The development of cancer models that mimic the native tumor microenvironment (TME) complexities is critical to not only develop effective drugs but also enhance our understanding of disease progression. Here we establish and characterize our 3D in vitro engineered prostate cancer tissue model with tunable matrix stiffness, that is inspired by this study's spatial characterization of in vivo prostate tumor xenograft stiffness. Notably, our model's mimicry of the TME is further augmented by the inclusion of matrix remodeling fibroblasts to introduce cancer-stromal cell-cell interactions. This study addresses a critical unmet need in the field by elucidating the prostate tumor xenograft stiffness range and establishing a foundation for recapitulating the biomechanics of site-of-origin and soft tissue metastatic prostate tumors in vitro . Graphical abstract: Image, graphical abstract